2020
DOI: 10.1002/cptc.202000038
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Diethyl‐Phosphonic Acid Anchoring Group Affects the Charge‐Separated State on an Iridium(III) Complex Functionalized NiO Surface

Abstract: Cyclometalated Iridium(III) complexes, i. e. [Ir(C N)2(dppz)][PF6], bearing either two or four ‐CH2PO(OH)2 anchoring groups (IrP2dppz or IrP4dppz) are explored as photosensitizers for p‐type dye sensitized solar cell (DSSC). The synthetic route is described and the iridium(III) complexes are characterized with respect to their electrochemical and photophysical properties. The modified anchoring ligand geometry exploited in this work not only alters the electronic nature of the complex (that is by destabilizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 67 publications
3
7
0
Order By: Relevance
“…Poldme et al found 9 nmol cm −2 for RuPd. These values are similar in magnitude to other systems with typical anchoring groups such as phosphonic acid and carboxylic acid (Pellegrin et al, 2011;Wahyuono et al, 2020).…”
Section: Photoelectrocatalysis On Niosupporting
confidence: 79%
“…Poldme et al found 9 nmol cm −2 for RuPd. These values are similar in magnitude to other systems with typical anchoring groups such as phosphonic acid and carboxylic acid (Pellegrin et al, 2011;Wahyuono et al, 2020).…”
Section: Photoelectrocatalysis On Niosupporting
confidence: 79%
“…In contrast, the LUMO energy levels are distributed across the anchoring N^N groups [ 26 , 57 ]. The phosphonate anchoring groups establish a stronger chemical linkage to the TiO 2 surface, thereby tuning the LUMO energy level and enhancing the water-splitting hydrogen generation [ 45 ]. The energy level of Ir1 and Ir3 are quite the same, as predicted by PL data previously ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies on Ir(III) cyclometalated complexes have found that different anchoring groups on N^N ligands are used to achieve highly efficient and stable water-splitting systems [ 44 , 45 ]. Incorporating anchoring groups, including carboxylate, or phosphonic acid, into the bipyridine ligand structure of [Ir(C^N) 2 (N^N)]⁺-type dyes [ 45 ] facilitates their stable attachment to semiconductors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electronic structure of the interface is mainly responsible for the charge transport characteristic. , However, often an energy discontinuity across the interface hinders the barrier-free transport of holes from the organic active layer to the valence band of NiO . It has been shown that covalent surface grafting can be a useful strategy to control the electronic properties of the surfaces of inorganic semiconducting materials, thereby improving the overall efficiency of devices. , Phosphonic acid (PA) molecules are widely used surface modifiers, especially in tailoring the surfaces of transition metal oxides (TMOs), such as indium tin oxide and TiO 2 , as the PAs easily form a self-assembled monolayer (SAM) on the surfaces of TMOs. This ability provides several advantages, such as increasing the long-term stability of air-exposed surfaces and adjusting the work function and surface energy to the desired level. ,, As for NiO, however, several works have been focused on tuning the properties of NiO surfaces via a SAM of PAs. ,,, It should be emphasized that most of these works are purely experimental reports, and a fully atomistic understanding of PA grafting on the NiO surface is still lacking. Specifically, there are three questions to be answered: (a) How do PAs adsorb on the NiO surface?…”
Section: Introductionmentioning
confidence: 99%